Analysis of MSME Benefits (Case Study: Fitri Busana Pasar Raya MMTC Deli Serdang) - Fikri Ardiansyah Pulungan; Jeremi Putranta Tampubolon; Nova Novita Pardede (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to know the description of Fitri Busana's business and to know the financial condition of Fitri Busana's business. The method used in this research is a survey method. The data collected includes secondary data and primary data. Secondary data was obtained by direct interviews with business owners Fitri Clothing while secondary data was obtained from books and internet sites related to research. The results showed that Fitri Busana received a profit of IDR 9,000,000 in one month which was enough to meet her daily needs with her family. For the progress of the Fitri Clothing business and to increase profits, it is recommended to maintain quality, quality, service to consumers so that this business continues.